Evaluation of the Fiqh Learning Process - Lutfi Alfarizi (Journal of Social Science Utilizing Technology, 2023)
Background. The learning process is one of the things that needs to be considered in education. If the process is good, it is likely that the results that will be obtained will also be good. To achieve optimal learning outcomes, a maximum learning process is needed. In a learning process, every educator and learner should be familiar with the process. Because knowing about a learning process, will make educators and students understand the purpose and objectives of learning. So that the learning process is not lame. Purpose. the purpose of this study was to determine the results of the evaluation of fiqh learning in MA Asy-Syafi'iyah Bangsalsari Jember. Method. In this study, researchers used qualitative methods. Qualitative research methods are research methods used to research on natural object conditions, where the researcher is the key instrument, data collection techniques are triangulated, data analysis is inductive, and qualitative research results emphasise meaning rather than generalisation . Results. The result of this research is the learning of Fiqh material at MA Asy-Syafi'iyah Bangsalsari Jember is good. The educators are linear with the subject, very supportive of the learning process. So that the learning process in MA Asy-Syafi'iyah runs well and maximum. Conclusion. Evaluation is something that is very urgent in the world of education. It needs to be done regularly. The existence of this mini research, of course, is to find out how the learning process has taken place during one semester. By paying attention to the process, the results of interviews from teachers, and student report cards, researchers have been able to conclude that, learning Fiqh material at MA Asy-Syafi'iyah Bangsalsari Jember is good.